Digital human modeling and applications in health, safety, ergonomics and risk management : healthcare applications : 10th International Conference, DHM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings.: healthcare applications : 10th International Conference, DHM 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, proceedings. Part II ([2019]) - Unknown
No abstract available